CO2 Enhanced Oil Recovery in Heterogeneous Porous Media: An Experimental Investigation - Al-bayati, Duraid Mohammed Attieya (Curtin University, 2020)
This research has focused on providing a deep understanding of the effects of reservoir heterogeneity on performance of CO2-EOR using a systematic laboratory investigation. The result are insightful in revealing and quantifying the pronounced effects of a number of factors such as interlayer crossflow, degree of heterogeneity, injection scheme and flooding mode on the outcome of this EOR method. The information generated can have important implications for numerical simulation of the technique at reservoir scale.